Determinants of Finance Performance of State-Owned Enterprises (BUMN) Banking Using Data Panel Regression - Mulyani, Mulyani; Fitriani, Yasinta (Accounting and Business Journal, 2022)
The purpose of this study was to determine whether there is an effect of Capital Adequacy Ratio (CAR), Net Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Expenses and Operating Income (BOPO) on the profitability of state -owned banking companies listed on the IDX. simultaneously and partially. The sample in this study were 7 banking companies listed on the IDX whose financial statement data were listed on the Indonesia Stock Exchange for the 2015- 2020 period. Data analysis using Panel Data Regression Test, hypothesis testing using the coefficient of determination (R2), simultaneous test (F test) and partial test (t test) with data processing using the Eviews 6 program. The results show that from the coefficient of determination test (R2) obtained by 0.0587 or 5.87% shows that the variables CAR, NPF, FDR and BOPO are able to explain their existence to the Net Profit Margin (NPM) variable on profitability while the remaining 94.13% is explained by other variables not examined. In addition, the simultaneous test of the CAR, NPF, FDR and BOPO variables together has no effect on the level of profitability. Partially, the Capital Adequacy Ratio variable has a positive but not significant effect on profitability. Net Performing Financing has a positive but not significant effect on profitability. Financing to Deposit Ratio has a positive but not significant effect on profitability and Operating Expenses and Operating Income have a positive but not significant effect on profitability in banking companies listed on the IDX